Errata : a book of historical errors - Alles, Hemesh (New York : Green Tiger Press, 1992)
Twelve plates illustrate scenes from great civilizations of the past, from a Zulu wedding to Egyptians farming by the Nile. Each plate contains ten deliberate errors or anachronisms to test the reader.
Keywords: Civilization, Ancient; Picture puzzles; Civilization, Ancient; Picture puzzles